Household Laundrette / Noor Haslinda Abd Halil and Erna Marina Redzuan - Abd Halil, Noor Haslinda; Redzuan, Erna Marina (Faculty of Artistic and Creative Technology, 2002)
Household Laundrette is not yet a popular business in this country. After realizing that it is a good thing to start the business in the new millenium. Most of an entrepreneur take an opportunity to open a household Laundrette because the competition is not much.